Implementation of the PPKM Policy in the Context of Handling Covid-19 in Cimahi City, West Java Province - Tri Hendratmoko; Andreo Wahyudi Atmoko (Budapest International Research and Critics University, 2022)
The purpose of this study is to assess the Implementation of Community Activity Restrictions (PPKM) in Cimahi City, as well as the variables that promote and limit its implementation. This research employs a qualitative, descriptive method. Through interviews, observations, and documentation, data were gathered. Emergency PPKM was implemented in Cimahi City from 3 to 20 July 2021 as a follow-up to Micro PPKM, including the phases of socialization, preparation, implementation, and assessment. Emergency PPKM in Cimahi City includes the following: restrictions in the workplace, implementation of online teaching and learning activities, regulation of operating hours in various essential sectors, restrictions on activities and operating hours for restaurants/warung/ and similar businesses, restrictions on the capacity of places of worship, enforcement of strict health protocols in public facilities and social activities, and continued implementation of the 5M Health Practise. The supporting factors for the implementation of Emergency PPKM in Cimahi City are the existence of a PPKM derivative based on Minister of Home Affairs No. 15 of 2021 into a Decree of the Mayor of Cimahi, which regulates the Cimahi City Covid-19 Task Force, the availability of a budget based on Perwali No. 44 of 2021, the availability of human resources, and the public's willingness to comply with health protocols. The inhibiting factors for implementing Emergency PPKM in Cimahi City are the existence of the Cimahi City area as a transit city, the presence of travel agents, and the level of community saturation with PPKM rules.